Review of Challenges in Performing Real-World Evidence Studies for Nonprescription Products - Maihöfner C; Mallick-Searle T; Vollert J; Kalita P; Sood Sethi V (Pragmatic and Observational Research)
Christian Maihöfner,1 Theresa Mallick-Searle,2 Jan Vollert,3 Pranab Kalita,4 Vidhu Sood Sethi5 1Department of Neurology, General Fürth Hospital, University of Erlangen, Fürth, Germany; 2Division of Pain Medicine, Stanford Health Care Pain Management Clinic, Palo Alto, CA, USA; 3Department of Clinical and Biomedical Sciences, Faculty of Health and Life Sciences, University of Exeter, Exeter, UK; 4Global Category Medical Affairs, Haleon Plc, Weybridge, England, UK; 5Global Medical Affairs, GSK Consumer Healthcare Singapore Pte. Ltd, SingaporeCorrespondence: Vidhu Sood Sethi, GSK Consumer Healthcare Singapore Pte Ltd (Co Regn No. 201309040M), 23 Rochester Park #03-02, 139234, Singapore, Tel +6596447203, Email vidhu.x.sethi@haleon.comAbstract: In recent years, regulatory authorities have signaled a willingness to consider real-world evidence (RWE) data to support applications for new claims and indications for pharmaceuticals. Historically, RWE studies have been the domain of prescription drugs, driven by the fact that clinical data on patients are routinely captured in medical records, claims databases, registries, etc. However, RWE reports of nonprescription drugs and supplements are relatively sparse due to methodological gaps in this area. The objective of this narrative review is to identify which RWE methodologies have been used to study nonprescription products. A total of 49 articles were included based on literature searches. Label comprehension studies, used to support prescription-to-nonprescription switches, are useful in determining how nonprescription products will be used; however, they provide no actual clinical data. The most common RWE studies of nonprescription products were cross-sectional surveys, which investigated a broad range of indications and were conducted in an array of settings, including online, by phone, point-of-sale (pharmacy), outpatient clinics, and shopping malls. However, while this type of study is effective for identifying use patterns and attitudes in the general population, recall bias limits the ability to collect safety and effectiveness data. Studies of electronic medical records and claims databases are hampered by incomplete or absent capturing of data on nonprescription products. As a result, most RWE studies to date have provided limited useful information. Although case reports and expert opinion should not be discounted, in the absence of other information they provide few actual data. Novel approaches using smartphone apps and artificial intelligence may provide new opportunities to collect RWE for nonprescription products, but these areas of research are in their infancy. Overall, there is a need to develop standards for execution of RWE studies of nonprescription products in terms of endpoints, study design, and study quality.Keywords: cross-sectional studies, dietary supplements, evidence-based practice, nonprescription drugs, research design